A Small Molecule Modulator of Prion Protein Increases Human Mesenchymal Stem Cell Lifespan, Ex Vivo Expansion, and Engraftment to Bone Marrow in NOD/SCID Mice123. (15th May 2012) - Mohanty, Sindhu T.; Cairney, Claire J.; Chantry, Andrew D.; Madan, Sanjeev; Fernandes, James A.; Howe, Steven J.; Moore, Harry D.; Thompson, Mark J.; Chen, Beining; Thrasher, Adrian; Keith, W. Nicol; Bellantuono, Ilaria
Abstract: Human mesenchymal stem cells (hMSCs) have been shown to have potential in regenerative approaches in bone and blood. Most protocols rely on their in vitro expansion prior to clinical use. However, several groups including our own have shown that hMSCs lose proliferation and differentiation ability with serial passage in culture, limiting their clinical applications. Cellular prion protein (PrP) has been shown to enhance proliferation and promote self‐renewal of hematopoietic, mammary gland, and neural stem cells. Here we show, for the first time, that expression of PrP decreased in hMSC following ex vivo expansion. When PrP expression was knocked down, hMSC showed significant reduction in proliferation and differentiation. In contrast, hMSC expanded in the presence of small molecule 3/689, a modulator of PrP expression, showed retention of PrP expression with ex vivo expansion and extended lifespan up to 10 population doublings. Moreover, cultures produced a 300‐fold increase in the number of cells generated. These cells showed a 10‐fold increase in engraftment levels in bone marrow 5 weeks post‐transplant. hMSC treated with 3/689 showed enhanced protection from DNA damage and enhanced cell cycle progression, in line with data obtained by gene expression profiling. Moreover, upregulation of superoxide dismutase‐2 (SOD2) was also observed in hMSC expanded in the presence of 3/689. The increase in SOD2 was dependent on PrP expression and suggests increased scavenging of reactive oxygen species as mechanism of action. These data point to PrP as a good target for chemical intervention in stem cell regenerative medicine. STEM CELLS 2012;30:1134–1143